2022
DOI: 10.1039/d2nj02113g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly encapsulation of vanadium tetrasulfide into nitrogen doped biomass-derived porous carbon as a high performance electrochemical sensor for xanthine determination

Abstract: A self-assembly strategy was presented in this work for the synthesis of vanadium tetrasulfide nanospheres (VS4) embedded into nitrogen-doped biomass-derived porous carbon materials (abbreviated as VS4@N-BPC) utilizing birch bark as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The XRD patterns indicate the phase purity of the as-synthesized VS 4 nanodendrites, and all the characteristic major peaks are in good agreement with the pure phase of the standard XRD powder pattern of VS 4 (PDF no. 21-1434) without notable impurities. , The main XRD peaks at 15.8 and 17° correspond to the (110) and (020) diffraction planes. As shown in the FTIR spectrum of the as-synthesized VS 4 nanodendrites (Figure S1), the peaks at 545 and 990 cm –1 share a striking resemblance to the v (V–S–V) doubly bonded S 2– , doubly bridged S 2– , and the v (VS) terminal S stretches, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD patterns indicate the phase purity of the as-synthesized VS 4 nanodendrites, and all the characteristic major peaks are in good agreement with the pure phase of the standard XRD powder pattern of VS 4 (PDF no. 21-1434) without notable impurities. , The main XRD peaks at 15.8 and 17° correspond to the (110) and (020) diffraction planes. As shown in the FTIR spectrum of the as-synthesized VS 4 nanodendrites (Figure S1), the peaks at 545 and 990 cm –1 share a striking resemblance to the v (V–S–V) doubly bonded S 2– , doubly bridged S 2– , and the v (VS) terminal S stretches, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although VS 4 submicrospheres with peroxidase activity have been previously synthesized for colorimetric detection of Lcysteine 25 and self-assembled encapsulated VS 4 nanospheres' nitrogen-doped porous carbon was also reported for electrochemical detection of xanthine, 26 its chemiluminescent application has never been reported.…”
mentioning
confidence: 99%
“…The raw and modified materials were characterized by pH at the zero point of charge, Fourier transform infrared spectroscopy, scanning electron microscopy, energy dispersive x-ray, X-rays diffraction, Raman spectroscopy, Brunauer-Emmett-Teller/Barrett-Joyner-Halenda analysis, 13 C NMR, and Thermogravimetry analysis couple to differential scanning calorimetry, in order to confirm the effect of calcination. It was found that ACCP has as specific surface area of 306.33 m 2 g À 1 , it is charged negatively in a solution with pH > 3.150 and charged DPV 20.0-80.0 5.30 [46] CD-Au-NPs/XO-ADA [b] CV 310.0-6800.0 150.0 [32] X n O x /nano-CaCO 3 /GCE [c] CV 0.025-2.0 2.0 [21] MIP/p(L-ser)/GCE [d] DPV 1-100 0.547 [47] VS4@N-BPC/GCE [e] DPV 0.092-163.6 0.053 [48] Au/OMCS/GCE [f] DPV 0.10-20 0.006…”
Section: Discussionmentioning
confidence: 99%
“…The amperometric analysis had a linear detection range for xanthine ranging from 1 to 120 μM, having a detection limit of 0.5 μM. Recently, development of an electrochemical biosensor using vanadium tetrasulfide nanospheres (VS 4 ) fixed into nitrogen-doped biomass-derived porous carbon materials (VS 4 @N-BPC) was reported for electrochemical xanthine determination [ 146 ].
Figure 5 ( i ) Scheme showing the CAT/PLL/f−MWCNTs/GCE preparation [Adapted with permission from ref.
…”
Section: Nanomaterial-based Biosensors For Metabolites Detectionmentioning
confidence: 99%